Infraestruturas, narrativas e imaginários algorítmicos : tecnografando o preço dinâmico da Uber - Ana Gonçalves Guerra (2021)
The aim of this dissertation is to technograph the algorithmic agencies associated with Uber's surge pricing through their rhetorical/narrative, material/infrastructural and affective/imaginary dimensions. More specifically, we investigate these agencies by assessing how they produce and affect ways of managing and experiencing labor. Guided by the Foucauldian notion of "dispositif", we articulate a dispositional perspective that considers algorithmic agencies' integration into a heterogeneous and dynamic network composed of a variety of actors and explore to the power relations and fields of knowledge that make up these agencies, considering both Uber’s claims about surge pricing and algorithms, and the perceptions of those whose experiences are involved and affected by them: Uber drivers. We operate this dipositional perspective through technography, analyzing inscriptions that materialize surge pricing and algorithmic agencies, and anchor them in situated practices. Through this movement, we seek to understand when, and under what circumstances, algorithms emerge as a decisive agency in the practices and discourses that organize the work of drivers. This research is based primarily on theoretical and methodological contributions linked to Platform Studies and Critical Algorithms Studies. Based on this framework, we present the conceptualization of algorithms and algorithmic power that informs our study. The analysis of the rhetorical/narrative dimension of surge pricing revealed the articulation of the algorithm's promise of objectivity to an ideal self-regulated market. In the exam of the material/infrastructural dimension we explored Uber's technological solutions that subsidize the operationalization of surge pricing through datafication of territories and anticipation of future dynamics. The affective/imaginary dimension emphasizes drivers' everyday encounters with surge pricing, as well as affects, strategies and ways of knowing that emerge from this encounters. Finally, in the concluding remarks, we weave these three analytical dimensions guided the dispositional perspective and offer e some notes on the precarity and the uncertainties that constitute Uber driver’s algorithmic labor.